"Guerra de todo o povo": a influência das lutas políticas e sociais na nova doutrina de defesa nacional venezuelana - Buzetto, Marcelo (2011)
The focus of this research is the strategic importance of national defense in the development of so-called "Bolivarian Revolution", a process underway in Venezuela. We intend to use as a reference several theoretical works that are in the field of Marxism, and authors who, while not having total affinity with this current of contemporary thought, made a significant contribution to the study of Art of War and the Theory of Strategy. The key to our work will be an evaluation of the Bolivarian New Military Doctrine and its relation to the strategy known as "War of All the People" (WAP). We also seek to check what are the contradictions and innovations brought about by the process of political, economical and social transformation in Venezuela for the study of national defense in an anti-imperialist perspective